Adequacy of prenatal care and associated factors in the State of Rio Grande do Sul, Brazil - Adami, Aline De Gregori; Motta, Leonardo Rapone da; Sperhacke, Rosa Dea; Kato, Sérgio Kakuta; Pereira, Gerson Fernando Mendes; Rahmi, Rosa Maria (Revista de Saúde Pública, 2023)
OBJECTIVE: This study aims to assess the degree of adequacy of prenatal care (PNC) in the state of Rio Grande do Sul (RS) and in its 7 macro-regions considering the time of PNC initiation and the number of appointments attended. It also aims to verify the mode of delivery prevalence and the factors associated with PNC adequacy by mode of delivery. METHODS: Sub analysis from a cross-sectional study conducted among 13,432 childbearing women aged 15–49 years assisted in 66 maternity hospitals of the Unified Health System (SUS) and private associated facilities from September 2017 to October 2019. A standardized form was used to collect sociodemographic data, and information about PNC and delivery from the childbearing women’s prenatal cards, hospital records, and medical reports. RESULTS: The PNC coverage was (98.4%), but only 57.5% of the participants had an adequate PNC defined as the one initiated until the 12th gestational week, with attendance of at least 6 appointments. The cesarean rate was 57.2%. Among women who performed vaginal delivery, multivariate analysis showed that for each 1-year increase in the age of the parturient, the chance of having an adequate PNC increased by 5%. White parturients with higher education and fewer deliveries residing in the macro-region of Valleys were more likely to have an adequate PNC when compared with non-white parturients, who were illiterate and/or had incomplete elementary school, with 3 or more deliveries and who resided in other macro-regions. During pregnancy, 96.0% of the women performed at least one anti-HIV test, 55.8% a rapid test for syphilis, and 75.0% a Venereal Disease Research Laboratory test (VDRL). CONCLUSIONS: Despite the almost universal PNC coverage in RS, the PNC offered by the SUS was adequate for just half of the population, therefore public health policies targeted at women receiving care in this setting shall be revisited.